NAFTA Largely Responsible for the Obesity Epidemic in Mexico - Alana D. Siegel (Washington University Journal of Law & Policy, 2016)
This note examines the link between the obesity epidemic in Mexico and NAFTA. Siegel argues that NAFTA’s leniency towards Foreign Direct Investments as well as its limitations on governmental regulation has impeded Mexico’s ability to address detrimental public health concerns, directly contributing to their obesity epidemic. Siegel then attempts to reconcile the desire for free trade with public health regulation by proposing changes to NAFTA’s language in order to create the flexibility necessary to directly address public health concerns.
Keywords: NAFTA; Obesity; Mexico; Foreign Direct Investments; Public health; Regulation; Free trade; Globalization; WTO